2019
DOI: 10.1002/lio2.297
|View full text |Cite
|
Sign up to set email alerts
|

Lingual frenuloplasty with myofunctional therapy: Exploring safety and efficacy in 348 cases

Abstract: Background Ankyloglossia is a condition of altered tongue mobility due to the presence of restrictive tissue between the undersurface of the tongue and the floor of mouth. Potential implications of restricted tongue mobility (such as mouth breathing, snoring, dental clenching, and myofascial tension) remain underappreciated due to limited peer‐reviewed evidence. Here, we explore the safety and efficacy of lingual frenuloplasty and myofunctional therapy for the treatment of these conditions in a large and diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
64
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 41 publications
0
64
0
12
Order By: Relevance
“…The range in the lingual frenulum morphology is created by variabilityon a spectrum -of several factors 1,2 . Ankyloglossia is characterized by a restriction of tongue movements 1,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The range in the lingual frenulum morphology is created by variabilityon a spectrum -of several factors 1,2 . Ankyloglossia is characterized by a restriction of tongue movements 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Tongue movements are essential for the performance of orofacial functions. It must be highlighted that tongue elevation is needed for proper tongue rest posture, for adequate nasal breathing, swallowing and production of the sounds [t], [d], [n], [l] e [ɾ] 3,4 . An important aspect to remember is that protrusion of the tongue is not required for sucking, swallowing, breathing, chewing, and speaking.…”
Section: Introductionmentioning
confidence: 99%
“…14 Ankyloglossia has been linked to sleep difficulties and sleep apnea in children and adults. [15][16][17] A tongue-tie prevents the tongue from resting on the palate. This lack of tongue to palate suction, especially during sleep, allows the tongue to fall into the pharynx at night and restrict or obstruct the airway and leads to sleep-disordered breathing or sleep apnea.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of tongue to palate suction, especially during sleep, allows the tongue to fall into the pharynx at night and restrict or obstruct the airway and leads to sleep-disordered breathing or sleep apnea. 17,18 In a recent systematic review, myofunctional therapy was shown to retrain the tongue to properly rest on the palate and prevent it from occluding the airway. 19 Children achieved a 62% decrease in the apnea-hypopnea index (AHI), and adults attained a 50% decrease in the AHI.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies left out of the CCS may have helped otolaryngologists understand the importance of tongue physiology, appreciate updated techniques and treatment protocols to achieve improved results, and better understand outcomes. 2-5…”
mentioning
confidence: 99%